Population, Sex Ratios and Development in Greenland - Hamilton, Lawrence C.; Rasmussen, Rasmus Ole (ARCTIC, 2010)
During the 20th century, Greenland society experienced a dramatic transformation from scattered settlements based on hunting, with mostly turf dwellings, to an urbanizing post-industrial economy. This transformation compressed socioeconomic development that took centuries to millennia elsewhere into a few generations. The incomplete demographic transition that accompanied this development broadly followed the classical pattern, but with distinctive variations relating to Greenland’s Arctic environment, sparse population, and historical interactions between two cultures: an indigenous Inuit majority and an influential Danish minority. One heritage from Danish colonial administration, and continued more recently under Greenland Home Rule, has been the maintenance of population statistics. Time series of demographic indicators, some going back into the 18th century, provide a uniquely detailed view of the rapid hunting-to-post-industrial transition. Changing sex ratios—an early excess of females, shifting more recently to an excess of males—reflect differential impacts of social, economic, and technological developments. Au cours du XXe siècle, la société du Groenland a connu une transformation dramatique, passant ainsi de peuplements de chasse éparpillés composés principalement d’habitations en tourbe à une économie urbanisée post-industrielle. Cette transformation a eu pour effet de comprimer le développement socioéconomique qui s’était échelonné sur des siècles, voire des millénaires ailleurs, en quelques générations. La transition démographique incomplète qui a accompagné ce développement a largement suivi le modèle classique, en étant toutefois assortie de variantes distinctives en ce qui a trait à l’environnement arctique du Groenland, à sa population rare et aux interactions historiques entre deux cultures : une majorité indigène inuite et une minorité danoise influente. Le maintien de statistiques sur la population découle de l’administration coloniale danoise, ce qui se continue en vertu de l’autonomie ...